Stimulated expression of ELR+ chemokines, VEGFA and TNF-AIP3 promote mycobacterial dissemination in extrapulmonary tuberculosis patients and Cavia porcellus model of tuberculosis. (July 2022) - Davuluri, Kusuma Sai; Singh, Amit Kumar; Kumar, Vimal; Singh, Shoor Vir; Singh, Ajay Vir; Kumar, Santhosh; Yadav, Rajbala; Kushwaha, Shweta; Chauhan, Devendra Singh
Abstract: Pathogenic mycobacteria induce and accelerate blood vessel formation driven by extensive inflammation during granuloma formation, which is a central feature of mycobacterial pathogenesis. Tumor necrosis factor-alpha (TNF-α) enhances the expression of vascular endothelial growth factor (VEGF) and glutamic acid-leucine-arginine (ELR+) chemokines, which are potent inducers of vascularization. Most of the reported research work contends that VEGF growth factor induces neovascularization in human tuberculosis (TB) patients, but the evidence is inconclusive. Considerable ambiguity exists concerning the factors responsible for miliary tuberculosis. To identify such factors, we proposed an alternative explanation that could be found in miliary tuberculosis (MTB) cases. We performed a comparative analysis of angiogenic factors TNF-α, VEGF, and angiogenic ELR+ CXC and CC chemokine ligands in extrapulmonary tuberculosis (EPTB) and pulmonary tuberculosis (PTB) patients. To observe the relationship of these factors with the severity of bacterial burden, guinea pigs were infected with Mycobacterium tuberculosis (M.tb) and levels of the angiogenic factors were examined at different time intervals. Expression of these factors also exhibited a significant positive correlation with bacterial burden in other organs like the spleen, liver, and lymph nodes. We demonstrated statistical data on bacterial burden at different time points following the dissemination of infection in guinea pigs. In this study, we observed that there was a stimulated increase in the expression of ELR+ chemokines and VEGF in EPTB patients as compared to PTB patients. Following increased dissemination, the host immune response clears bacteria from the lungs during disease progression in guinea pigs. Highlights: Disease especially in the cases of extra pulmonary TB requires potent therapeutic strategies. Targeting dissemination mechanisms induced by Mycobacterium tuberculosis control spread of infection. This may be the first attempt to describe the pathways chosen by MTB bacilli for its dissemination. Stimulated expression of ELR+ chemokines and VEGF seen in Extrapulmonary tuberculosis patients. ELR+ chemokines, VEGFA and TNF-AIP3 might be useful as biomarkers to monitor dissemination.